Dynamics of MUI’s Fatwa on Zakat al-Fitr Paid in Qimah: Analysis of Guidelines for Issuing Fatwas - Ahmad Mafaid; Nawir Yuslem; Dhiauddin Tanjung (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
The MUI’s fatwa regarding zakat fitrah through qimah raises some dynamics and contradictions. The fatwa issued by the North Sumatra MUI in 2008, the Aceh MPU in 2014, and the DKI Jakarta MUI in 2018 have different decisions that give rise to contradictions at first glance. Through a literature study using the descriptive analytical method, this study aimed to unravel the dynamics of the fatwa of zakat al-fitr through bimah and analyze it based on the MUI fatwa stipulation guidelines. The results showed that the fatwa issued differed from the procedures for establishing a fatwa. In the MUI fatwa guidelines, it is stated that MUI and Regional MUI fatwa decisions, which are based on predetermined guidelines, have equal status and do not cancel each other, and if there are differences between MUI and Regional MUI fatwa decisions regarding the same issue, a meeting between the two leadership councils needs to be held to find the best solution. This study recommended that the Central MUI review the fatwa of zakat fitrah through bimah and guidelines for establishing fatwas.